Properties of Calcium Hydroxyapatite Formed Using Waste Oyster Shell and Ammonium Dihydrogen Phosphate - MOHD SAM, MAS FATIN ELYKA (Enhanced Knowledge in Sciences and Technology, 2022)
The properties of calcium hydroxyapatite formed using waste oyster shell and ammonium dihydrogen phosphate was recorded in this research. Muar is also well-known for its oyster farming, and the principal component of oyster shell is calcium carbonate impurities. Calcium Hydroxyapatite is a biomaterial that may be extracted from waste. The aims of this research were to prepare calcium hydroxyapatite from a stoichiometry mixture of waste oyster shell properties of selected calcium hydroxyapatite samples using scanning electron microscopy. The waste oyster shell was dried at for 24 hours before being heated at 700°C and sintered at 1000°C for 2 hours. To guarantee high homogeneity and fine powder samples, the heat-treated waste oyster shell was ground and sieved < 50 µ. OriginLab was used to calculate the mass loss of Calcium Hydroxyapatite The impact of sintered at 1000°C was analyzed using Fourier Transform Infrared (FTIR), X-ray diffraction (XRD), AccuPyc II 1340 gas displacement pycnometer and COXEM EM-30 Scanning Electron Microscopy (SEM). Calcium carbonate is predicted to be extracted from waste oyster shells, and it is expected that it’s properties will be analyzed when mixed with Ammonia Dihydrogen Phosphate.